Ilustrated Versión of the Law # 693 The Law of Sovereignty Food Security and Nutrition - Zeledón Zeledón, Dora Odely; FAO; Zeledón Zeledón, Dora Odely (Nicaragua 2013)
Bibliografia- The National Assembly of Republic of Nicaragua presents to hhe citizenship the ilustrated version of the law No. "Law of sovereigty and Food security and Nutrition
Ilustrated Versión of the Law # 693 The Law of Sovereignty Food Security and Nutrition
Bibliográfia- incluye imagines narrativas en ingles
COL.SOC.
Keywords: SOCIOLOGÍA